Análise de um sistema de condicionamento de ar pelo ciclo de adsorção utilizando energia solar - Oliveira, Jefferson Alves (2015)
This dissertation presents an analysis of the performance of an cooling system by adsorption, powered by solar energy, focusing on the use of renewable energy. The Brazilian energy matrix is based mainly on water resources, and the increase in electricity consumption is necessary the expansion of fossil fuel use for this purpose, causing an increase in power tariff costs. In order to exploit renewable energy sources to reduce the consumption of fossil fuels, the use of solar energy applied to cooling cycles stands out with a promising option when considering the share of the consumption of electricity that the air conditioning and cooling represent. Within this context are presented the principles of operation of the air conditioning cycle by adsorption and solar collectors. The cooling system analyzed is located in the city of Chapada dos Guimarães, and basically consists of a set of solar collectors, heat reservoir and adsorption machine. The analysis of this system was divided on the solar energy capture and the circuits of air conditioning machine by adsorption and held for three different climatic conditions of solar radiation. The amount of thermal energy that is flowing through the system in order to identify the capacity of air conditioning system and to determine the efficiency of capture of solar energy and production of cold in each of these parts is calculated. The analyzed operation data show that the system in question is operating at below nominal power, mainly because the amount of thermal power supplied to the desorption process and the temperature of condensed water returning to the chiller.